EP-296 Introduction of an Information Leaflet for Patients Presenting with Hand Injuries. (9th August 2022) - Bowerman, Kathryn; Frost, Stephen; Agarwal, Reena
Abstract: Aim: Patient Information Leaflets (PILs) are an effective way to educate patients, involve them in their care, and improve communication between patient and clinician. Our department did not have a PIL covering all hand injuries in single leaflet, therefore we decided to make one. Method: We created a PIL to give to all patients with hand injuries that were seen in the Emergency Department by Plastic Surgery. The PIL explains what will happen if they need surgical intervention, or if the injury can be managed conservatively. In our hospital, Plastic Surgery covers hand injuries on Fridays, Saturdays, and Sundays and then patients are either planned for dedicated trauma lists during the week or for follow up in the Hand Trauma Review Clinic. Results: The leaflet detailed the follow up patients could expect, as well as red flag symptoms to look out for, and who to contact should any problems arise. The PIL enabled us to emphasise the importance of adherence to advice given by healthcare professionals, particularly on any dressings and splints provided to the patients. Conclusion: While the leaflet is generic in nature to cover all injuries, specific advice is given in addition to the leaflet to ensure that patients have the best possible care. In the future, we would like to make the leaflet electronic in order to reduce waste and risk of infection. Ideally, patients could scan a QR code taking them directly to the relevant part of the leaflet.